Pengaruh Sistem Manajemen Pembelajaran Virtual Berbasis Schoology Terhadap Disposisi Matematis Siswa - Suradi Tahmir; Nasrullah; Eka Hermia (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This study aims to show the effect of the use of virtual Learning Management System (LMS), namely schoology, on the mathematical disposition of students in learning mathematics. This research is classified as quasi experiment, which involves two classes given different treatments, the first class is treated using a virtual learning management system using schoology with a Blended Learning learning model and called an experimental class, while the second class is taught using a model direct teaching and is called the control class. The population in this study were all students majoring in class XI in one of the state high schools in Makassar. Sampling in this study using purposive sampling technique. For data collection, the instruments used were a mathematical disposition questionnaire (pre-test and posttest) and an observation sheet of the implementation of learning. The data was analyzed with descriptive statistical techniques and inferential statistics. The results of the study prove that the virtual learning management systems based schoology with blended learning models towards mathematical dispositions is better than direct teaching models.